The Effectiveness of Using Blended Learning on Increasing Students' Learning Independence and Critical Thinking Skills - Nababan, Damayanti; Saragih, Orde Koria; Sitanggang, Rawatri; Enjelina, Enjelina; Batubara, Irma (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to explore the effectiveness of the application of the Google Sites-based Blended Learning model in improving students' learning independence and critical thinking skills. With a qualitative approach and case study design, this study involved 12 students in the fourth semester of the Christian Religious Education Study Program at IAKN Tarutung who participated in the Curriculum Development lecture. This research uses a qualitative approach with a case study type that aims to explore in depth students' experiences, views, and beliefs towards the use of Google Sites in Blended Learning strategies. Data collection techniques were carried out through direct observation, individual interviews, and structured group interviews. Data analysis follows five stages of the cycle, namely compiling, disassembling, reassembling, interpreting, and concluding. The results of the study show that Blended Learning is able to encourage students to learn independently by managing time, choosing learning resources, and designing reflective learning strategies. In addition, students show improvements in critical thinking, such as openness to new ideas, the ability to make decisions, seek relevant information, and analyze problems systematically. However, some students still have difficulty in identifying the root of the problem as part of solving the problem. These findings indicate that Blended Learning is not only effective as a technical strategy, but also as a holistic pedagogical approach in 21st century skills development. This study suggests the need for training on independent learning strategies and strengthening problem-solving to optimize technology-based learning outcomes in higher education.